Microbial models of mammalian metabolism: O-dealkylation of para-alkoxybiphenyls. - Smith, R V (1982)
The potential of selected microorganisms to O-dealkylate alkyl aryl ethers in a manner analogous to mammalian systems has been studied. A total of 45 fungi and actinomycetes were screened for their ability to O-demethylate 4-methoxybiphenyl. Of the 20 organisms found to actively metabolize this substrate, 5 were chosen for additional study. Incubation with a series of five homologous 4-alkoxybiphenyls, 4-methoxy-, 4-ethoxy, 4-(1-propoxy)-, 4-(2-propoxy)-, and 4-(1-butoxy)biphenyl, revealed that all were O-dealkylated by Aspergillus flavus ATCC 24741. With Triton X-100 as a solubilizing agent, the relative rates and extent of O-dealkylation of the 4-alkoxybiphenyls, were studied with A. flavus. The methoxy and ethoxy dervatives were dealkylated in more than 90% yield after 72 h of incubation, while the higher homologs were cleaved to the extent of only about 10%. An analogous pattern of O-dealkylation has been reported in mammalian systems.